EXPLORING ICT EDUCATION AT MASTER LEVEL IN THE CONTEXT OF ADVANCEMENT OF DIGITAL ECOSYSTEM: THE CASE OF KAZAKHSTAN - Ahrens, Andreas; Gruenwald, Norbert; Zascerinska, Jelena; Zakirova, Gulnara; Yefimova, Irina; Kakabayev, Anuarbek; Melnikova, Julija; Aleksejeva, Ludmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In order to achieve the aim of Kazakhstan’s progressive development of the digital ecosystem, higher education sector has to harmonize ICT study programmes in accordance with updated professional standards and industry requirements for preparation of specialists. As competencies and skills permanently change, competencies and skills are to be enhanced lifelong. The purpose of the paper is to explore ICT education in the context of advancement of digital ecosystem underpinning empirical analysis of ICT education at master level in Kazakhstan and elaboration of a new research question. The method of the study is exploratory case study. The case study was carried out in December 2017. The findings of the empirical study reveal that a combination of Data Science and Information Security emerge in the context of the advancement of digital ecosystem in Kazakhstan. The new research question has been formulated: What are core courses of the hybrid study programme that combines Data Science and Information Security at master level? Directions of further research are proposed.